Effectiveness and impact of intravenous magnesium sulfate in spinal surgery systematic review and meta-analysis - Jin, Zhaoguo; Zhao, Jianyong (Frontiers in Pharmacology, 2025)
BackgroundEffective pain management following spinal surgery is crucial for preventing complications related to delayed mobilization. Magnesium sulfate (MgSO4) has shown promise as an analgesic agent, influencing neurotransmitter modulation and autonomic nervous system regulation. However, studies evaluating its effectiveness and safety in spinal surgery remain inconsistent, necessitating a comprehensive meta-analysis to assess its role.ObjectiveThis study aimed to perform a systematic meta-analysis to compare the safety and efficacy of magnesium sulfate against standard therapeutic options in spinal surgery.MethodsThe meta-analysis followed PRISMA guidelines. We performed data extraction and analysis using Review Manager version 5.4. The study population included patients undergoing spinal surgery, with the intervention group receiving intravenous magnesium sulfate at varying dosages or in combination with other agents. The comparison group received either a placebo or alternative treatments. Primary outcomes included pain intensity, opioid consumption, and safety parameters.ResultsTen randomized controlled trials involving 641 patients were included. Magnesium sulfate administration significantly reduced pain scores at 24 h (MD −0.18, 95% CI: −0.34 to −0.02) and decreased opioid consumption (SMD −0.34, 95% CI: −1.07 to −0.35). Additionally, a significant reduction in muscle relaxant usage was observed (SMD −0.91, 95% CI: −0.66 to −0.10). When compared with dexmedetomidine, magnesium sulfate improved verbal response (MD 1.22, 95% CI: −0.16–2.61) and prolonged extubation time (MD 0.91, 95% CI: −0.98–2.80). No significant differences in hemodynamic parameters (heart rate and blood pressure) were observed between the groups.ConclusionIntravenous magnesium sulfate demonstrated significant benefits in reducing postoperative pain and opioid consumption, while also improving verbal response and orientation. These findings suggest that magnesium sulfate may serve as a valuable adjunct in the perioperative management of spinal surgery patients. Further research is required to confirm these results and establish optimal dosing protocols.